An exploration of older worker flexible working arrangements in smaller firms. (14th April 2015) - Atkinson, Carol; Sandiford, Peter
Abstract : This article explores flexible working arrangements (FWAs) for older workers in smaller UK firms. We address three questions: how far older workers need and value FWAs, the type of FWAs they need, and whether smaller firms can offer these FWAs. We draw on 46 semi‐structured interviews from six smaller case study firms to present a qualitative exploration of both owner‐manager and (under‐researched) worker perspectives. We evidence the offer and importance of temporal and work‐role FWAs, together with the use of i‐deals and ad hoc FWAs in meeting the needs of this diverse group. We make three contributions: first, theoretically, in arguing for an extended definition of FWAs and understanding formality of offer; second, to practice, in highlighting FWA mechanisms appropriate to older workers; third, to policy, in questioning the effectiveness of both the business case approach to older worker FWAs in smaller firms and policy's positioning of older workers as a homogeneous group.